Traffic Analysis of Quality of Service (QoS) for Video Conferencing between Main Campus and Sub Campus in Laboratory Scale - Sudarsono, Amang; Siswanto, Anang; Iswanto, Heru; Setiawan, Qoirul (Politeknik Elektronika Negeri Surabaya (PENS), 2015)
Recently, in the distance learning system, video conferencing becomes one of expected course material delivery systems for creating a virtual class such that lecturer and student which are separated at long distance can engage a learning activity as well as face to face learning system. For this reason, the service availability and quality should be able to guaranteed and fulfilled. In this research, we analyze QoS of video conferencing between main campus and sub campus as the implementation of distance learning system in laboratory scale. Our experimental results show that the channel capacity or bandwidth of WAN connection between main campus and sub campus at 128 kbps is able to generate the throughput of video transmission and reception at 281 kbps and 24 kbps, respectively. Meanwhile, throughput of audio transmission and reception is 64 kbps and 26 kbps with the number of total packet loss for video and audio transmission is 84.3% and 29.2%, respectively. In this setting, the total jitter for video and audio transmission is 125 ms and 21 ms, respectively. In this case, there is no packet loss for traffic transmitting and receiving with jitter is not more than 5 ms. We also implemented QoS using Trust CoS model dan Trust DSCP for improving the quality of service in term of jitter up to 12.3% and 22.41%, respectively.Keywords: quality of service, throughput, delay, jitter, packet loss, Trust CoS, Trust DSCP